Implementasi Standar Pengelolaan Untuk Peningkatan Mutu Sekolah - Ayu Salina (Universitas Pakuan, 2026)
IMPLEMENTATION OF MANAGEMENT STANDARDS FOR SCHOOL QUALITY IMPROVEMENT This study examines the implementation of national management standards (Management Standards) to improve the quality of schools in two public elementary schools in Mataram City, Indonesia, namely SDN 15 Mataram and SDN 36 Mataram. Data were collected through participant observation, in-depth interviews with principals, teachers, and staff, and document analysis, then processed using interactive models of individual case analysis and cross-case analysis. Data validity is guaranteed through triangulation of sources and techniques. The findings show that although both schools experience a shortage of qualified educators, they differ in planning, implementation, and supervision results. SDN 15 Mataram shows more structured facility management and more frequent internal supervision, while SDN 36 Mataram is constrained by less strategic locations, infrastructure gaps such as the absence of libraries, and lower staff professionalism. To overcome these obstacles, the two schools have developed concrete follow-up plans: SDN 15 Mataram schedules regular principal-teacher mentoring and establishes numeracy learning corners, while SDN 36 Mataram prioritizes budget allocation for urgent facilities and expands extracurricular programs. The results of the study highlight the important role of school principal leadership in translating management standards into improving the quality of education.